Incidente de desconsideração de personalidade jurídica inversa nas sociedades limitadas - Picoli, Agatha Vicente (2024)
The disregard of legal personality is an essential legal institute in contemporary civil law, particularly in the context of business and family relations. This mechanism aims to curb fraud and abuses of rights, protecting the patrimonial autonomy of legal entities and ensuring the protection of creditors. Law No. 13,874/19, known as the Economic Freedom Act, reinforced the separation between the assets of legal entities and their partners, allowing for the disregard in cases of abuse of legal personality. Objective: The work aims to analyze the evidentiary elements considered by the Judiciary to accept requests for the disregard of legal personality in civil relations, based on patrimonial confusion and abuse of rights. By analyzing judicial decisions and doctrine, the study intends to understand the criteria and foundations that guide the application of this institute and is practical implications for the protection of creditors and the preservation of the patrimonial autonomy of legal entities. Methodology: The study was conducted through a bibliographic review method, documentary analysis of pertinent legislation and jurisprudence, and the study of specific cases. Results: The disregard of legal personality, both direct and reverse, requires a careful analysis of the specific case, considering the evidentiary elements that demonstrate fraud or abuse of rights. Brazilian jurisprudence has evolved towards establishing clear criteria for the application of this institute. Emblematic cases, such as the decision of the Superior Court of Justice that recognized the legitimacy of a partner to request the reverse disregard of legal personality, illustrate the importance of protecting the rights of the aggrieved parties